Activation of autophagy with PF-06409577 alleviates heatstroke-induced organ injury - Wei Zhang; Huajing Zeng; Siyu Xie; Cheng Yu; Meina Zhang; Qiuyan Chen; Huiyue Dong; Hui Zhang; Hao Lin; Nengjing Zheng; Lin Zhu; Jun Lu (Environment International)
Heat waves are a significant environmental issue threatening global human health. Extreme temperatures can lead to various heat-related illnesses, with heatstroke being among the most severe. Currently, there are no effective treatments to mitigate the multi-organ damage caused by heatstroke. We found that heat stress activated autophagy. Knockdown of the autophagy-related gene 7 (ATG7) or knockout of the autophagy initiation regulatory genes UNC-51-like autophagy activating kinase 1/2 (ULK1/ULK2) increased cell death. PF-06409577, an allosteric activator of AMP-activated protein kinase β (AMPKβ), reduced heat stress-induced cell death by promoting autophagy. Inhibition of ATG7 or ULK1 weakened PF-06409577′s protective effect on cells. Treatment of heatstroke mouse models with PF-06409577 suppressed high temperature-induced damage to multiple organs, including the liver, kidneys, lungs, and small intestine. PF-06409577 protected liver and kidney functions, lowered the expression of kidney injury markers neutrophil gelatinase associated lipocalin (Ngal), secreted phosphoprotein 1 (Spp1), and clusterin (Clu), and reduced levels of the inflammatory factor IL-6. Additionally, it decreased heat stress-induced macrophage infiltration and IL-6 production in the liver. The results indicate that activation of autophagy serves a protective function during heat stress, and the AMPK activator PF-06409577 exhibits potential in mitigating heatstroke-induced multi-organ damage through its ability to promote autophagy.